Retracted: Construction of visual evaluation system for building block night scene lighting based on multi‐target recognition and data processing - Xiaojian Wang; Xiaoye Sun; Zixuan Wang (IET Circuits, Devices and Systems)
Abstract The rapid development of night tourism economy has made people's demand for night scene lighting in architectural blocks increasing, and the night scene lighting situation of urban architectural blocks has gradually received people's attention and attention. Achieving good night lighting visual effects of building blocks can not only meet the needs of residents for entertainment and consumption at night, but also beautify the image of blocks and promote the economic development of building blocks. However, due to the unreasonable planning and management of the night scene lighting design of architectural blocks in some areas, improper application of night scene lighting, and overly commercial night scene lighting effects, it affects people's normal night activity needs and has a negative impact on the long‐term block economy of the region. Faced with this situation, the night lighting of architectural blocks and its problems is studied and photos are identified with high lighting visual effect evaluation using multi‐target identification and data processing to construct a night lighting visual evaluation system for architectural blocks, and also an experimental study of the visual evaluation system is conducted. The results show that the overall visual suitability evaluation support rate of the respondents for the night scene lighting of architectural blocks is 95.64%, and the visual evaluation system proposed in this paper is reasonable and effective, which is conducive to promoting the improvement of the visual effect of night scene lighting in architectural blocks.